18 Effects of Protein Concentration, Degradability, and Beta-adrenergic Agonists on Ruminal Microbial Communities in Finishing Heifers. (8th March 2022) - Pfau, Alison P; Samuelson, Kendall L; Henniger, Madison T; Hales, Kristin E; Lindholm-Perry, Amanda; Myer, Phillip R
Abstract: To improve animal performance and modify growth by increasing lean tissue accretion, beef cattle production has relied on use of growth promoting technologies such as beta-adrenergic agonists. These synthetic catecholamines, combined with the variable inclusion of rumen degradable (RDP) and undegradable protein (RUP), may improve feed efficiency and rate of gain in finishing beef cattle. However, the impact of beta-adrenergic agonists and protein level and source on the ruminal microbiome is limited. The objective of this study was to determine the effect of different protein concentrations and beta-adrenergic agonist (ractopamine hydrochloride; RAC) on ruminal bacterial communities in finishing beef heifers. Heifers (n = 140) were ranked according to body weight and assigned to pens in a randomized complete design to 6 different treatments, containing 3 protein treatments (Control: 13.9% CP, 8.8% RDP, and 5.0% RUP; High RDP: 20.9% CP, 13.4% RDP, 6.1% RUP; or High RUP: 20.9% CP, 9.1% RDP, 10.4% RUP) and 2 RAC treatments (0 and 400 mg/day). Rumen samples were collected from heifers by oral lavage 7 days before harvest. The DNA from the samples were sequenced to identify bacteria based on the V1-V3 hypervariable regions of the 16S rRNA gene using the Illumina MiSeq. Sequences and data from the treatments were analyzed using the R environment and PROC MIXED in SAS 9.4 (SAS Inst.; Cary, NC). Beta diversity was analyzed using PERMANOVA based on PCoA Bray-Curtis distances and were significant among the treatments (P < 0.05). Alpha diversity metrics such as Chao1 and Shannon diversity indices were not significantly different (P > 0.05). Differences among treatments at variable taxonomic levels after analyses through DESeq2 were significantly different for the main effects of protein and RAC, as well as their interaction (P < 0.05). These results suggest possible effects on the microbial communities, potentially acting synergistically to improve performance.